Diagnóstico y mejoramiento de la Gestión de Distribución en La Cervecería Bucanero S.A Sucursal Ciego de Ávila - Calvo Gutiérrez, Ariadna (Universidad Central "Marta Abreu" de Las Villas, 2011)
This research was carried out in the Bucanero Brewery Inc, Branch of Ciego de Avila; the company is located in the Universal Warehouse Inc, which is located in Ceballos Road, Km 1, belonging to CORALSA (according with the spanish acronym). The considered branch provides warehouse and distribution services of beers to several customers in the central provinces, reporting the highest levels of purchasing the Meliá Las Dunas (more distant), so the paper focuses on this customer, in order to know the profitability of the business. Based on the further explained, the aim of this research was to diagnose the Distribution Management in Bucanero Brewery Inc, Ciego de Ávila Branch, specifically with the customer Hotel Meliá Las Dunas, Santa María Key, Villa Clara, with a view to identifying main actions to be undertaken for improvement, using as tool the MVP (according with the spanish acronym). To comply with the general objective methods and techniques were used as the interview, literature review, search on Internet, amongst which were: Microsoft Excel, MS-Visio, MSProject. The research allowed the diagnosis of the current situation in the company, identifying the main problems that affect their development and proposing actions that contribute to increasing the key indicators.
Keywords: Cervecería Bucanero S.A. Sucursal Ciego de Ávila; CORALSA; Almacenes Universales S.A